A room-temperature liquid-metal composite anode for dendrite-free lithium-ion batteries. (March 2022) - Liu, Honghao; Zhang, Weixin; Tu, Ji; Han, Qigao; Guo, Yaqing; Sha, Wuxin; Wang, Fuhe; Tian, Jie; Zhao, Yuming; Tang, Shun; Li, Yan; Cao, Yuan-Cheng
Abstract: The room temperature liquid metal (LM) has great potential in the application of dendrite-free lithium-ion batteries (LIBs) as high-capacity anodes. LM anodes can achieve self-healing via reversible solid-liquid phase transition and inhibit the lithium dendrite due to the lithium affinity during cycling. A facile synthesis of liquid metal nanoparticles (LMNPs) has been developed via the generation of carbon-encapsulated Ga/Sn alloy composites. The 3D framework of LM composites has been observed by SEM imaging. Combined with gel polymer electrolytes in LIBs, the LM anodes delivered a high capacity of 750 mAh/g at a current density of 0.2 A/g and maintained the specific capacity of 500 mAh/g at 2 A/g with high active material loadings. This work provides an efficient way to achieve electrode materials possessing good interfacial compatibility and high specific capacity for LIBs. Highlights: The liquid metal nanoparticles (LMNPs) of the Ga/Sn alloy can be stabilized as nanospheres using the rGO/CNTs framework. Anodes based on the LMNPs with high active material mass loading (7.3-9.3 mg/cm 2 ) have been prepared and investigated. High capabilities of 750 mAh/g at 0.2 A/g and 500 mAh/g at 2 A/g are achieved by using the LMNPs as anodes.